Black hispanics have a worse cardiovascular risk profile than mixed hispanics in Venezuela. - Ryder, Elena; Silva, Eglee; Sulbarán, Tulio; Fernández, Virginia; Campos, Gilberto; Calmon, Gustavo; Clavell, Emilio; Raleigh, Xiomara; Florez, Hermes (Investigación Clínica, 2009)
In order to characterize components of the metabolic syndrome (MS) in Venezuelan black Hispanics and compare these metabolic abnormalities with those found in the predominant mixed Hispanic population, 2336 mixed Hispanics (69% women) and 281 black Hispanics (60 % women), aged 20-78 years, without prior history of diabetes and/or cardiovascular disease were evaluated in a population-based study in Zulia State, Venezuela. Blood pressure (BP), waist circumference, as well as fasting insulin, fasting blood glucose (FBG), triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C) levels were measured. The criteria proposed by the National Cholesterol Education Program/Adult Treatment Panel III (NCEP/ATP III) to identify those with metabolic abnormalities were used. We found that black Hispanics showed higher frequency of age-adjusted elevated BP than mixed Hispanics in both men (66.9% vs. 52.3%, p < 0.01) and women (39.3% vs. 30.4%, p < 0.05). In men, elevated FBG was also more frequent in black Hispanics (32.7%) than in mixed Hispanics (22.3%), despite the lack of significant differences in fasting insulin, HOMA-insulin resistance and HOMA-beta cell function values. In women low HDL-C and higher abdominal obesity were more common in black Hispanics (71.8% and 54.1%, respectively) than in mixed Hispanics (56.2% and 44.5%, respectively), despite the greater frequency of high TG in mixed Hispanics (22.6%) when compared to black Hispanics (13.3%). Furthermore, in logistic regression analysis black Hispanic race was independently associated with higher risk for hypertension, fasting hyperglycemia, and low HDL-C. These results suggest that black Hispanics have worse cardiovascular risk profile than mixed Hispanics in Zulia State, with higher BP, higher FBG, more abdominal obesity, and lower HDL-C. Identification and intervention of these high-risk subjects are important strategies for diabetes and cardiovascular disease prevention in Venezuela.